THE EXTENT OF CORRESPONDENCE BETWEEN CURRICULUM AND SCIENCE CLASSIFICATIONS IN THE OTTOMAN STATE (16TH TO 19TH CENTURIES)* - İnce, Nazife (PEOPLE: International Journal of Social Sciences, 2018)
To develop an idea about the scientific developments in a particular field of a particular period, it is important to examine the types of sciences handled by scholars as well as the types of sciences involved in the school curriculum. This paper is trying to achieve an idea about the correspondence between the curriculum and the knowledge that had been produced in a specific field, which is Linguistics, and within specific era, which is from 16th to 19th century of the Ottomans. To do this, we are going to give a description about the school curriculum of language sciences and the widely accepted classification of language sciences among the Ottoman scholars, with a study on the extent of correspondence between the two. The examination of the correspondence between what the classification of sciences suggests and the ongoing application within schools would provide information about the Ottomans’ approach to Arabic language education and the general concept of linguistics at that era. It was seen that there was not a perfect correspondence between the fields of linguistic studies and the curriculum. One of the sub-outcomes of the research shows that the curriculum reflects only the language sciences which were defined as primary fields. To understand the reasons of this half-corresponding relation, similar studies about other eras need to be done.